PROSPECTS FOR THE USE OF ARTIFICIAL INTELLIGENCE IN LAW ENFORCEMENT AGENCIES IN THE NEW UZBEKISTAN - Khodjayev Farrukh Ismoil ugli (Journals Park Publishing, 2024)
This article explores the prospects of integrating artificial intelligence (AI) into law enforcement agencies in New Uzbekistan. It highlights the potential benefits of AI, including enhanced crime prevention and investigation capabilities, streamlined administrative processes, improved public safety through advanced surveillance, and data-driven decision-making support. The text also discusses the role of AI in training law enforcement personnel and emphasizes the importance of addressing ethical and legal challenges associated with AI implementation, such as algorithmic bias and data privacy concerns. Furthermore, it underscores the necessity of fostering public trust through transparency and community engagement. Overall, the document presents a comprehensive overview of how AI can modernize law enforcement in Uzbekistan while advocating for responsible and equitable use of technology.
Keywords: New Uzbekistan, Artificial Intelligence (AI), digital transformation, Law enforcement, government reports, Technology modernization, expert analysis, Crime prevention, Public safety, statistics.